Sleep apnoea-hypopnoea syndrome in the obese and non-obese: Clinical, polysomnographical and clinical characteristics - Elena Martínez Cuevas; Carmen Muñoz Peláez; Estrella Ordax Carbajo; Ana Isabel Navazo Eguia; Lourdes Martín Viñe; Aranzazu Prieto Jimeno; María Luz Alonso-Álvarez (Elsevier, 2021)
Introduction: Sleep apnoea-hypopnoea syndrome (SAHS) and childhood obesity are two high prevalence conditions that represent a public health challenge. Objective: To analyse the association between both and comparing child groups that had or did not have both conditions. Patients and methods: A prospective study in children (3-14 years), referred to the "Multidisciplinary Sleep Unit" due to suspected SAHS, between 1 November 2015 and 1 August 2017. The following parameters were evaluated: anthropometry, symptoms, blood pressure, ear, nose, and throat examination, polysomnography (nocturnal PSG) and laboratory tests. Results: A total of 67 children were evaluated (64% non-obese (NOb) and 36% obese (Ob). It was observed that the Ob were older (P < .001), slept less hours (P = .028), did less physical exercise (P = .029), ate less in the school dining room (P = .009), had la lower sleep efficiency, and had abnormal values in carbohydrate and lipid metabolism.The children with SAHS were younger (P = .010), a high percentage of daytime sleepiness (P = .001), and breathing through the mouth (P = .006), greater percentile of diastolic blood pressure (P = .019) and a lower IGF-1 (P = .003) than those that did not have SAHS. The comparison of the SAHS NOb and SAHS Ob groups, showed that the first group were younger (P = .010), snored more (P = .012), had a more severe SAHS (IAH 13.1 vs 5.4, P = .041), and a higher GOT (P < .001). In the second group, they slept less hours P = .038) and showed lower values of glucose (P = .039), insulin (P < .001), and HOMA (P < .001). Conclusion: The behaviour of SAHS is different in obese children and non-obese children, with differences in age, clinical characteristics, severity of SAHS, and metabolic changes. The children diagnosed with SAHS were in the higher percentile of diastolic blood pressure. Obesity was associated with worse sleep quality, and changes in carbohydrate and lipid metabolism. Resumen: Introducción: El síndrome de apneas-hipopneas del sueño (SAHS) y la obesidad infantil son dos entidades con alta prevalencia que constituyen un problema de salud pública. Objetivo: Analizar la interacción entre ambas, comparando grupos de niños que presentaban o no ambas condiciones. Pacientes y metodología: Estudio prospectivo en niños (3-14 años), remitidos a la ''Unidad Multidisciplinar de Sueño'' por sospecha de SAHS, entre el 1/11/2015 y el 1/08/2017. Se evaluaron los siguientes parámetros: antropometría, síntomas, tension arterial, exploración otorrinolaringológica, polisomnografía (PSG nocturna) y studio analítico. Resultados: Se valoraron 67 niños, 64% no obesos (NOb) y 36% obesos (Ob).Se observó que los Ob tenían más edad (P < ,001), dormían menos horas (P = ,028), realizaban menos ejercicio físico (P = ,029), comían menos en comedor escolar (P = ,009), tenían menor eficiencia del sueño y presentaban valores alterados en el metabolismo hidrocarbonado y lipídico.Los niños que presentaba SAHS tenían menor edad (P = ,010), un mayor porcentaje de somnolencia diurna (P = ,001) y respiración bucal (P = ,006), mayor percentil de tensión arterial diastólica (P = ,019) y menor IGF-1 (P = ,003) que los que no presentaban SAHS.La comparación de los grupos de SAHS NOb frente SAHS Ob, reveló que los primeros eran de menor edad (P = ,010), roncaban más (P = ,012), tenían mayor severidad del SAHS (IAH 13.1 vs 5.4, P = ,041) y mayor GOT (P ≤ ,001) y en el segundo grupo, se objetivó que dormían menos horas (P = ,038) y mostraban valores mayores de glucosa (P = ,039), insulina (P < ,001) y HOMA (P < ,001). Conclusión: El comportamiento del SAHS es diferente en los niños con y sin obesidad, presentando diferencias en la edad, características clínicas, severidad del SAHS y alteraciones metabólicas. Los niños con diagnóstico de SAHS tienen mayor percentil de tensión arterial diastólica. La obesidad conlleva una peor calidad de sueño y alteraciones en el metabolismo hidrocarbonado y lipídico.